Penempatan Kerja, Pengalaman Kerja dan Kinerja Karyawan - Maartje Paais (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2020)
The purpose of this study is to determine whether there is an effect of work placement and work experience on employee performance at PT. Various Marine Resources (ASTB) in Central Maluku Regency. The method used is multiple linear regression analysis. The sample used was 45 respondents using the Slovin formula. The results of this study indicate that the influence between work placement and work experience with employee performance, especially at PT. Various Sumber Tata Bahari (ASTB) In Central Maluku Regency, it is proven that there is a positive and significant influence between work placement and work experience on employee performance. The most dominant variable affecting the performance of employees at PT. Various Sources of Maritime Affairs (ASTB) in Central Maluku Regency is Work Experience. This is because work experience has a greater coefficient value than the job placement variable.